Are we hearing the voices? Africanisation as part of community development - Westhuizen, Marichen van der (HTS teologiese studies, 2017)
The aim of the article is to report on research findings that could contribute to the development of decolonised academic material. Africanisation of curricula implies that education and training as well as praxis be informed by the reality of the South African context, the viewpoints of the people of South Africa and their descriptions of what is needed to build a just society. This is relevant to a variety of service professions. This article was presented from a trans-disciplinary framework, and the term ‘professional carers’, including the social service and theology professions, was used. The discussion explored how academia can approach the development of curricula that will inform praxis and which is relevant to the African context. The terms ‘Africanisation’, ‘decolonisation’ and ‘contextualisation’ were linked, whereafter a developmental approach to the development of the content and presentation of academic material was proposed. The article is concluded with recommended strategic options for the development of Africanised curricula.